Comparative binding and uptake of liposomes decorated with mannose oligosaccharides by cells expressing the mannose receptor or DC-SIGN. (January 2020) - Gao, Haifei; Gonçalves, Cristine; Gallego, Téo; François-Heude, Marc; Malard, Virginie; Mateo, Véronique; Lemoine, François; Cendret, Virginie; Djedaini-Pilard, Florence; Moreau, Vincent; Pichon, Chantal; Midoux, Patrick
Abstract: Mannose Receptor (MR) and DC-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) are two mannose-specific targets for antigens carried by liposomes but DC-SIGN is more specific of DCs. Here, DC targeting is addressed by using DPPC/DOPE liposomes decorated with a series of diether lipids with a polar head of either a mannose (Man), tri-antenna of α-d -mannopyranoside (Tri-Man), [Manα1-3(Manα1-6)Man] (Man-tri), pseudo-Man4 (PMan4 ) or pseudo-Man5 (PMan5 ). Liposomes decorated with Man-Tri show the highest binding and internalization in cells expressing DC-SIGN and in human monocytes-derived DCs. Conversely, cells expressing MR bind and take up Tri-Man liposomes 3-fold higher than Man-tri liposomes. Comparatively, liposomes decorated with PMan4 and PMan5 do not show any advantages. Overall, the results indicate that liposomes decorated with Man-tri residues are more selective toward DCs than those with Tri-Man thanks to better recognition by DC-SIGN. Graphical abstract: Image 1 Highlights: Liposomes decorated with Man-Tri show higher binding and internalization than Tri-Man liposomes in cells expressing DC-SIGN. Conversely, cells expressing MR bind and take up Tri-Man liposomes 3-fold higher than Man-tri liposomes. Thus, liposomes decorated with Man-tri residues would be more selective than Tri-Man to target DCs.